Application of a "Continuous‐Acquisition‐Method" to potassium isotope measurements by multi‐collector inductively coupled plasma mass spectrometry. (11th May 2021) - Gu, Hai‐Ou; Sun, He; Huang, Chao; Wang, Fangyue; Ge, Can
Abstract : Rationale: The very small mass difference between 41 K and 40 ArH + makes the flat, hydride interference‐free peak shoulders very narrow (0.002–0.003  m/z unit), bringing a number of analytical challenges when measuring K isotopic compositions by multi‐collector inductively coupled plasma mass spectrometry (MC‐ICP‐MS). In traditional Sequence Run mode, the parameters are loaded every line of the sequence which can introduce tiny drifts of tune parameters and mass peaks. This may occasionally lead to the failure of K isotope measurements when mass drifts exceed 0.002  m/z unit. It is thus essential to keep the tune parameters, especially the magnet current, very stable to achieve high‐precision K isotopic compositions. Method: We developed a "Continuous‐Acquisition‐Method" (CAM) MC‐ICP‐MS Run mode to improve the stability when determining K isotopes. Two sets of experiments were designed: (a) Stability test: measuring a single pure K solution (viz. NIST‐999c) for ~3 h and comparing the stability of the two run modes; and (b) GSB‐K test: measuring our inhouse pure K standard solution (GSB‐K) in both run modes and comparing the accuracy and precision. Results: The traditional Sequence Run mode only kept the MC‐ICP‐MS system stable for the first ~1.5 h during the ~3‐h test, with an offset of the mass peaks of ~0.003  m/z unit. The CAM Run mode yielded higher stability during the whole test (~3 h), with a peak shift <0.0004  m/z unit. Measurement of the GSB‐K standard solution in Sequence Run and CAM Run modes gives identical δ 41 K values when the magnet was kept stable, with the CAM Run mode offering a better precision and keeping the instrument stable for longer time. Conclusions: The MC‐ICP‐MS CAM Run mode shows higher stability and better precision. It is, therefore, good for high‐precision K isotope measurements.